ANALYSIS OF USING QUIZIZZ TO THE STUDENTS OF GRADE XII SMK N 1 SURABAYA USING THE TECHNOLOGY ACCEPTANCE MODEL - Puji Lestari; Jaka Nugraha (Jurnal TAM (Technology Acceptance Model), 2021)
The use of learning aid media in this pandemic era is very necessary to support the running of online schools to run smoothly. One of the supporting media for the teaching and learning process is quizizz application.  The purpose of this study was to analyze the understanding of the use of learning applications in high school. This study adopted the Technology Acceptance Model (TAM) by incorporating the perception of pleasure, perception of ease, benefit perception to the behavior to use. Sampling techniques are based on probability sampling using slovin formula. This study involved 126 people from 178 populations of class XII OTKP who had used quizizz application at SMK N 1 Surabaya. Analysis using Structural Equation Modeling – Partial Least Square (SEM PLS) through Smart PLS software version 3. By using 2 PLS calculation models namely measurement models (outer models) and structural models (inner models). These findings show that the perception of pleasure has a positive effect on the user's attitude, the perception of ease of negative effect is not significant to the user's attitude, the perception of usefulness has a significant positive effect on the user's attitude, and the perception of ease of having a significant positive interest in the intention of use through the perception of usability. This research shows that perceptions of usefulness, perceptions of ease, and perceptions of pleasure are strong predictors of behavior to use.